NUMERICAL STUDY ON THE BEHAVIOUR OF TOP STORY INTERIOR BEAM-COLUMN JOINTS ON STEEL SPECIAL MOMENT FRAMES - Pratiwi, Naomi; Tjahjanto, Helmy Hermawan; Adriel, Gregorius Nathan (Applied Research on Civil Engineering and Environment (ARCEE), 2025)
In steel special moment frames (SMFs), the strong-column–weak-beam (SCWB) principle is typically applied to ensure a sway mechanism with beam hinging. However, for interior joints in top stories, this approach may lead to uneconomical column sizes and unfavorable hinge formation. As an alternative, the strong-beam–weak-column (SBWC) principle may offer more practical solutions. This study investigates the seismic behavior of top-story interior joints in SMFs, introducing novelty by directly comparing the conventional SCWB philosophy with the alternative SBWC approach. Finite element models were developed in ABAQUS to simulate pushover loading conditions and evaluate hinge formation, loaddisplacement response, and panel zone deformation. Three joint configurations were analyzed to represent different design scenarios. Results show that SCWB joints achieve beam hinging as intended, but the distribution is not ideal due to unbalanced stiffness at the top story. SBWC joints develop plastic hinges in the column with more symmetrical yielding, though accompanied by higher shear demands in the panel zone. These findings suggest that SBWC criteria may be applied in top-story interior joints as a viable and more economical alternative to SCWB, provided that panel zone plastic deformation is explicitly addressed in design.